Coherent Growth of α-Fe2O3 in Ti and Nd Co-doped BiFeO3 Thin Films. Issue 3 (2nd July 2016) - Zhang, Huairuo; Marincel, Daniel M.; Trolier-McKinstry, Susan; Rainforth, W. Mark; Reaney, Ian M.
Abstract : Coherent dendritic α-Fe2 O3 precipitates were observed to form at the surface of epitaxial films of (Bi0.75 Nd0.25 )(Fe0.97 Ti0.03 )O3 (BNFO) grown by pulsed laser deposition. The Fe2 O3 dendrites are assemblages of nanosized particles with an approximate length of 500 nm. Through the use of atomic resolution scanning transmission electron microscopy, a transition zone at the BNFO/α-Fe2 O3 interface, ∼2 unit-cells wide, was observed to be Fe2 O3 -rich with the perovskite structure. It is proposed that the formation of the Fe2 O3 -rich perovskite structure encourages epitaxial growth of the α-Fe2 O3 rather than the formation of the incoherent Fe2 O3 particulate second phase frequently reported in BiFeO3 -based thin films. Impact Statement The discovery of the new structure may explain the abnormally high ferromagnetic response observed in the BiFeO3 -based single-phase epitaxial films, and will benefit the communities of materials science. GRAPHICAL ABSTRACT: